Recent Magnetometric Researches at Zoltan, Covasna County. Some Observations Regarding the Limits and Inner Structure of the Noua Settlement in the Place Called “Nisipărie” - Popa, Alexandru (Analecta Archaeologica Ressoviensia, 2017)
Previous field researches in the location called Zoltan-“Nisipărie” revealed a settlement with several different cultural layers, among which those of the Noua Culture seem to be dominant. Along the past years researchers have conducted both systematic archaeological diggings as well as geophysical researches. Through the scientific research presented in the following report we set out to highlight the limits and structure of the settlement with the help of magnetometry. The results we obtained allow us to outline the eastern limit of the intensely inhabited settlement. Judging by the magnetic anomalies we identified, we can speak about a large number of pits that stand at the basis of the archaeological structures found in the Noua settlement at Zoltan “Nisipărie”.